Extraordinary PR, ordinary budget : a strategy guide - Farmer, Jennifer R. (Berrett-Koehler Publishers, 2017)
Explaining that you don need a big budget to make a big impact, this book shows you that, no matter how modest your budget, you can build a cost-effective communications strategy that will help you break through the noise in an information-overloaded world. --